Víctor Fraiz Villanueva. Process to the FETE and the republican school - De Gabriel Fernández, Narciso (Historia y Memoria de la Educación, 2020)
The repression exerted by the Franco regime on teachers mainly affected people with a left-leaning ideology who defended Republican secularism. This circumstance was quite common among the members of the Spanish Federation of Education Workers, especially among the organization’s leaders. One of these leaders was Víctor Fraiz Villanueva, a native of Pontevedra, who was court-martialed twice because of his political, union and teaching activities. He was tried in 1934 and again in 1937, and was eventually executed by a firing squad. This article examines the last three years of his life.